Prevalence of depressive symptoms in the elderly people assisted at the family health units and associated factors - Kelly Thais Pestana Bespalhuk; Luana Ferreira Coelho Vieira; Priscila Aguiar Mendes; Annelita Almeida de Oliveira Reiners; Rosemeiry Capriata de Souza Azevedo; Ana Carolina Macri Gaspar Vendramini (Universidade Federal de Santa Maria, 2021)
Objective: to analyze the prevalence of depressive symptoms in elderly people assisted at Family Health Units and associated factors. Method: This is a cross-sectional study carried out with a clipping of research in 2015 with a proportional stratified probabilistic sample of 557 elderly people assisted at Family Health Units in Tangará da Serra. The independent variables are sociodemographic and health conditions. The dependent variable is depressive symptoms and it was assessed using the depression scale. Poisson regression verified the associated factors. Results: the prevalence of depressive symptoms was 22.8%. The associated variables were: regular/bad/terrible health perception (PR = 6.69; CI: 3.78-11.82); functional dependence (PR = 2.99; CI: 1.85-4.83) and not having a job (PR = 3.96; CI: 1.02-15.38). Conclusion: the prevalence of depressive symptoms was higher than in other studies. Social factors and related to the health conditions of the elderly person are associated with depressive symptoms, and it is important to develop actions to promote active and healthy aging.